2023
DOI: 10.1002/fft2.310
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum J26 postbiotics alleviate high‐fat and high‐cholesterol diet‐induced hypercholesterolemia via regulating the LXRα‐CYP7A1‐bile acid‐excretion pathway

Miao Zheng,
Ming Ma,
Linge Wang
et al.

Abstract: Postbiotics have received increasing interest for their storage stability and safety compared to probiotics, as well as their potential functionality. In this study, edible Lactobacillus plantarum J26 postbiotics (J26P) were prepared by spray drying using skimmed milk as the medium, and 1113 compounds were identified. The aim of this study was to evaluate the cholesterol lowering effect of J26P on hypercholesterolemic mice induced by a high‐fat and high‐cholesterol diet (HCD). The results suggest that J26P sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…This strain has been associated with various fermented products, such as fermented chayote, chili pepper, milk, passion fruit beverages, and quinoa. The L. plantarum, renowned for its versatile probiotic properties, plays a crucial role in various sectors, such as the food industry, feed production, and clinical medicine . However, as an industrialized strain and a probiotic within the human digestive tract, L.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This strain has been associated with various fermented products, such as fermented chayote, chili pepper, milk, passion fruit beverages, and quinoa. The L. plantarum, renowned for its versatile probiotic properties, plays a crucial role in various sectors, such as the food industry, feed production, and clinical medicine . However, as an industrialized strain and a probiotic within the human digestive tract, L.…”
Section: Introductionmentioning
confidence: 99%
“…1−5 The L. plantarum, renowned for its versatile probiotic properties, plays a crucial role in various sectors, such as the food industry, feed production, and clinical medicine. 6 However, as an industrialized strain and a probiotic within the human digestive tract, L. plantarum inevitably faces numerous stresses from the external environment. 7 These stresses encompass acid stress and freezing stress during formulation, as well as encounters with gastric acid and bile salts within the human gastrointestinal system.…”
Section: Introductionmentioning
confidence: 99%
“…Bile acids (BAs) are steroidal substances synthesised from cholesterol by the liver, which bind to plasma proteins and enter the circulation, where they are distributed to organs throughout the body. Approximately 95% of BA is reabsorbed in the ileum and recirculated back to the liver, and FXR is a key regulator of the hepatic‐intestinal circulation of bile acids (Zheng et al, 2023). Previous findings by X et al (Zheng et al, 2021) showed that porcine bile acid analogues in the ileum activate both TGR5 and inhibit FXR, promote intestinal GLP‐1 synthesis and secretion, and lower blood glucose.…”
Section: Introductionmentioning
confidence: 99%